The effect of annealing on ZnO:Al thin film growth on preparatory glass substrate by dc magnetron sputtering. (November 2019) - Sugianto, S; Astuti, B; Firmahaya, N A; Aryanto, D; Isnaeni
Abstract: Al doped ZnO (or ZnO:Al) thin films were deposited onto a preparatory glass substrate using dc magnetron sputtering. The effect of annealing time was 0, 30 and 50 minutes onto the structural, morphological, optical properties and electrical properties of the ZnO:Al films have been investigated. Thin films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), photoluminescence (PL) and I-V measurements, respectively. XRD measurement showed that each sample had an amorphous structure. The morphology of the film was more homogeneous when annealed in 50 minutes. PL characterization showed two emission peaks, namely blue emissions at a wavelength of 447 nm and red emissions at a wavelength of 752 nm. ZnO:Al film with an annealing time of 50 minutes had a higher blue emission PL intensity than other films.